Numerical modeling and synchrotron diffraction measurements of residual stresses in laser powder bed fusion manufactured alloy 625. (April 2022) - Malmelöv, Andreas; Hassila, Carl-Johan; Fisk, Martin; Wiklund, Urban; Lundbäck, Andreas
Graphical abstract: Highlights: A mechanism-based material model was applied to model residual stresses. Synchrotron diffraction was used to measure residual stresses of AM material. The full ring fitting method was compared with the sin 2 ψ method. The measured and computed residual stress field agree qualitatively very well. The effect on texture is small when varying the laser power and scanning speed. Abstract: Residual stresses in metal additive manufactured components are a well-known problem. It causes distortion of the samples when removing them from the build plate, as well as acting detrimental with regard to fatigue. The understanding of how residual stresses in a printed sample are affected by process parameters is crucial to allow manufacturers to tune their process parameters, or the design of their component, to limit the negative influence of residual stresses. In this paper, residual stresses in additive manufactured samples are simulated using a thermo-mechanical finite element model. The elasto-plastic behavior of the material is described by a mechanism-based material model that accounts for microstructural and relaxation effects. The heat source in the finite element model is calibrated by fitting the model to experimental data. The residual stress field from the finite element model is compared with experimental results attained from synchrotron X-ray diffraction measurements. The results from the model and measurement give the same trend in the residual stress field. In addition, it is shown that there is no significant difference in trend and magnitude of the resulting residual stresses for an alternation in laser power and scanning speed.